Experimental characterization of consensus protocol for decentralized smart grid metering. (January 2016) - Capriglione, Domenico; Ferrigno, Luigi; Paciello, Vincenzo; Pietrosanto, Antonio; Vaccaro, Alfredo
Abstract: The availability of intelligence at substation level, combined with the adoption of pervasive communication networks, offers technologies and opportunities to decentralized smart grid metering and control. In this domain self-organizing sensor networks equipped by distributed consensus protocols have been recognized as an effective enabling paradigm. The performance of these protocols is usually evaluated in simulation environments without considering the effects of real measurement transducers, data acquisition systems and communication systems. Attention is rarely paid to the influence of factors such as: the measurement uncertainty of the transducers, the effect of the limited bandwidth available on real radio systems, and the change of performance when real nodes enter and exit from the network during or among consensus procedure. The large scale deployment of this paradigm asks for comprehensive analysis aimed at assessing the impact of the non-idealities characterizing the real power system environment on the cooperative protocols performance. Armed with such a vision this paper aims at characterizing the performance of distributed consensus protocols in presence of uncertainty and non-ideality of the measurement instruments, of the measurement process and of the communication channel in a smart grid environment. Results obtained in simulation and real scenarios might be helpful hints in the implementation and use of this protocol in real networks.